SIFAT DAN MAKNA GERAKAN TARI EMPRAK DALAM INSPIRASI PENCIPTAAN TATA RIAS - Piwi, Adela Sanya; Usodoningtyas, Sri; Megasari, Dindy Sinta; Kusstianti, Nia (Jurnal Tata Rias, 2024)
Emprak dance is a dance that originates from Blitar. Emprak means busking from house to house with gending dishes. The Emprak dance has distinctive movements such as Kebyok entrok right and left and Srisig. The make-up for the Emprak Dance currently functions to beautify the dancer, while researchers aim to create a unique make-up while providing insight to future researchers so they can help preserve it. Regional dances so as not to be eroded. The methods used for this research are quantitative methods and qualitative methods. Starting with making the make-up design for the Emprak Dance, the design is based on the original make-up from the Emprak Dance, following trends and based on the meaning of the movements of the Emprak Dance. Observations were made regarding the most preferred designs, the suitability of colors for the Emprak Dance makeup, the shape of the Emprak Dance makeup, the harmony of the makeup with the clothing and describing the meaning of the Emprak Dance makeup. The most preferred design for the Emprak Dance makeup was design 5, as chosen. by 38 respondents. The color that is suitable for this make-up is red, which is in accordance with the meaning of the Emprak Dance. Design 5 is also considered the most harmonious with the Emprak Dance clothing. The red color in Emprak Dance makeup means love, lust, strength. courage, primitive attraction, danger, sin, sacrifice, and vitality.